A Privacy-Preserving Protocol for Network-Neutral Caching in ISP Networks - Davide Andreoletti (IEEE Access, 2019)
By performing in-network caching, Internet Service Providers (ISPs) allow Content Providers (CPs) to serve contents from locations closer to users. In this way, the pressure of content delivery on ISPs' network is alleviated, and the users' Quality-of-Experience (QoE) improved. Due to its impact on QoE, caching has been recently considered as a form of traffic prioritization in the debate on Network Neutrality (NN). A possible approach to perform NN-compliant caching consists in assigning the same portion of cache storage to all the CPs. However, this static subdivision does not consider the different popularities of the CPs' contents and is therefore inefficient. Alternatively, the cache can be subdivided among the CPs proportionally to the popularity of their contents. However, CPs consider this information private and are reluctant to disclose it. In this work, we propose a protocol to perform a popularity-driven subdivision of the caches' storage in a privacy-preserving and network-neutral fashion. The protocol is based on the Shamir Secret Sharing (SSS) scheme and is designed to ensure a NN-compliant subdivision of the caches while preserving the privacy of both CPs and ISP (i.e., contents' popularity and caches' size are not disclosed). Through dynamic simulation, we show that the popularity-driven cache subdivision (enforced by using our protocol) outperforms several baseline approaches in terms of overall network Resource Occupation (RO) and caching Hit-Ratios. Thanks to our numerical results, we observe that the frequency of execution of the protocol has a significant impact on the RO, and that the ISP can tune this frequency to minimize its RO while introducing an acceptable data overhead. Because of this tuning, several CPs may experience a loss with respect to the hit-ratio that they would obtain by independently choosing the frequency of execution. This loss is very limited, and the employment of the protocol is therefore beneficial to all the involved parties, especially since, by using it, CPs are guaranteed that the ISP behaves in a network-neutral manner.